IDENTIFIKASI STRUKTUR BAWAH PERMUKAAN MENGGUNAKAN METODE GEOLISTRIK KONFIGURASI SCHLUMBERGER AREA PANAS BUMI KENDALISODO KECAMATAN BERGAS KABUPATEN SEMARANG - Alchacindy Guenergar; Udi Harmoko; Sugeng Widada (Youngster Physics Journal, 2014)
The research has been done by using geoelectric method schlumberger configuration at Kendalisodo geothermal manifestation . The purpose of researching is to know layer of subsurface structure which control Kendalisodo geothermal manifestation.Measurement has been conducted using schlumberger configuration. The data observation conducted at 4 points  around by Kendalisodo hot springs . Data processing conducted using software IP2WIN. Data measurement in the field are potential differences and currents which can be used to calculate apparent resistivity value. After apparent resistivity value is created then processed using IPI2WIN program to know resistivity value in each layer with geology information validation. The results of the study showed seven  geoelectric layer of rock that is composed of layers of topsoil, sandstone, breccia, tuffan sandstone, breccia, tuff, and  combined Sandstone and breccia with resistivity values and different thicknesses. Interpretation of manually indicate the presence of  down faults that are weak zone where the fluid surface discharge.Keywords : geoelectric, geothermal, and Kendalisodo